Characteristics of good practice in food technology. (HMSO, 1996)
This publications in intended to help schools to implement food technology as part of the National Curriculum for design and technology. It identifies the characteristics of good practice in Key Stages 1 to 4 and describes the content of the food technology curriculum in those schools where standards were high. In addition, it contains and industrial perspective which helps set work covered in the food technology curriculum within a broader, realistic context of commercial food manufacture.